Keanekaragaman Jenis dan Karakteristik Habitat Burung di Ekosistem Mangrove Indramayu - Nurdin Nurdin; Dede Kosasih; Toto Supartono; Nurul M Ghojali; Haydar Rahardian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2021)
Karangsong mangrove forest area is the result of rehabilitation then used as the location of ecotourism by Pantai Lestari groups. The purpose of this research is to know and analyze the diversity of bird species, and to know the habitat conditions of birds related to environmental factors. The research was conducted in the mangrove ecotourism area of Karangsong in two types of habitat, namely mangrove and beach habitat types. This reserch used the Indeks Point of Abundance (IPA) method and the MacKinnon list method of 10 species in collecting the data. The data were collected with the strip transect method for vegetation and the area species curve method with a sample plot of 10x10 meters.The result of this, of resear her found there were 20 species of bird from 7 family, which 16 species were found in mangrove habitat types and 4 species in coastal habitat types. The number diversity index (H') of waterbirds obtained is categorized as moderate with a value of 1.95. In vegetation analysis, the researcher found 9 type of vegetasi in mangrove and coastal habitat. Retrieval of data on environmental factors including weather with sunny condition, then the temperature and humidity ranges from 31-34.1 and 18% -74%, similarity (pH) 1.7-7.4, salinity obtained  26%  -30%,  disturbance  which were  found,  Those are  the activities  of ecotourism visitors, transportation (motorboats passing around the research location), fish anglers, and the activities of pond farmers.